RE-VISITING EDWARD ALBEE’S THE ZOO STORY IN THE CONTEXT OF GEORGES POLTI’S FIRST SITUATION FROM HIS CANONICAL LIST OF DRAMATIC SITUATIONS: A DIVERGING AND ALLEGORICAL READING - Zafer ŞAFAK (Fırat University, 2019)
The Zoo Story narrates the incidental encounter of Jerry and Peter in Central Park. Jerry, who is a counter-culture antihero, is exhausted out of the indifference of society and its lack of human affection. He tries unsuccessfully to relate his uneasiness to non-committal smug Peter. His invasion of Peter’s personal space first leads him verbal abuse of and psychological assaults to Peter, which ends up with the unintentional physical attack by Peter himself. The Zoo Story still addresses to the taste of the present day audience as it did for that of the modern particularly when it is re-interpreted in the context of Georges Polti’s canonical The Thirty-Six Dramatic Situations. In it, Polti, who acknowledges his debt to Italian playwright Carlo Gozzi in the encapsulation of all the alleged dramatic situations, have found thirty-six dramatic situations which he argues that they succinctly include all the potential situations with their multifarious modifications and combinations. In it, it is put forward that the first dramatic situation Supplication is not ripe for the taste of the modern audience since it was not cultivated enough by such men of letters as Corneille and Shakespeare. Claiming that the first situation has been forgotten, Polti hastily skips the next situation and omits the significance of the first one. As opposed to Polti’s assertion, in the study, it is argued that the first situation complies with Albee’s play and it attempts to re-visited The Zoo Story in terms of the first situation. By demonstrating that the play has far-reaching metaphorical and allegorical intimations in accordance with the first situation, the study also aims to display revitalizing power of the